Brain Tectal Tumors: A Flexible Approach. Issue 3 (5th June 2018) - Perin, Alessandro; Galbiati, Tommaso Francesco; Casali, Cecilia; Legnani, Federico Giuseppe; Mattei, Luca; Prada, Francesco Ugo; Saini, Marco; Saladino, Andrea; Riker, Nicole; DiMeco, Francesco
Abstract: BACKGROUND AND IMPORTANCE: Mesencephalic tectal gliomas represent a subset of midbrain tumors, which are more frequent in children than in adults. They usually become symptomatic when causing hydrocephalus by occluding the aqueduct. Because of their slow progression, due to their benign histology, they are characterized by a relatively good prognosis, although hydrocephalus might jeopardize patients' prognosis. Treatment is usually represented by cerebrospinal fluid diversion associated or not with biopsy. CLINICAL PRESENTATION: We report 2 illustrative cases of tectal gliomas in adults where endoscopic third ventriculostomy (ETV) and simultaneous endoscopic biopsy were obtained during the same operation by means of a single burr hole with a flexible endoscope. CONCLUSION: We recommend using this overlooked neurosurgical tool for such cases, since it allows the surgeon to safely perform an ETV, then judge whether biopsy can be done or not, without harming the patient, and possibly achieving an important piece of information (histopathological diagnosis) to manage this subset of oncological patients.